2019
DOI: 10.1212/wnl.0000000000007280
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and predictors of 7- and 30-day hospital readmissions to pediatric neurology

Abstract: ObjectiveHospital readmission is an important quality improvement measure that has not been well-studied in pediatric neurology. We examined predictors of 7-day and 30-day readmissions for pediatric patients hospitalized with a neurologic diagnosis.MethodsThis was a retrospective study of hospital readmission rates in pediatric neurology patients admitted to a tertiary children's hospital from January 2017 to December 2017. Inclusion criteria were age ≤18 years and a primary neurologic diagnosis on admission, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 14 publications
3
10
1
Order By: Relevance
“…The number of previous unplanned readmissions as well as emergency room/department visits within the prior 6 months are associated with increased risk of readmission, whereas the risk of readmission is reduced if the index visit is a planned encounter. These results are consistent with prior studies mostly in the general pediatric and adult populations [3,10,16].…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…The number of previous unplanned readmissions as well as emergency room/department visits within the prior 6 months are associated with increased risk of readmission, whereas the risk of readmission is reduced if the index visit is a planned encounter. These results are consistent with prior studies mostly in the general pediatric and adult populations [3,10,16].…”
Section: Resultssupporting
confidence: 93%
“…Previous studies have identified risk factors such as higher severity of illness, public health insurance, multiple antiepileptic drugs, intensive care admission, and seizures with major complication/comorbidity [3,8]. These findings are generally consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations